Kenaikan Berat Badan Selama Kehamilan terhadap Keberhasilan ASI Ekslusif - Puspita Sari, Anjelina; Romlah Romlah (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Background: Exclusive coverage in Indonesia has not reached the target, one of the reasons is the lack of nutritional status of mothers during pregnancy. This study aims to determine the relationship between weight gain during pregnancy and the success of exclusive breastfeeding. Method: This type of research uses observational analytics using a cross sectional design. The sampling technique was purposive sampling, with a total sample of 82 respondents. Data was taken by observation and retrospective data from the respondent's medical records. The analysis technique uses the Chi-Square test. Results: Statistical test results showed a significant relationship between weight gain during pregnancy and the success of exclusive breastfeeding (pv=0.001). Weight gain during pregnancy is very important because it must be monitored. This monitoring can be done when the mother visits ANC